2014
DOI: 10.1097/aln.0000000000000134
|View full text |Cite
|
Sign up to set email alerts
|

Patient Blood Management in Elective Total Hip- and Knee-replacement Surgery (Part 1)

Abstract: In hip- and knee-replacement patients (hemoglobin level, 10 to 13 g/dl), even with a restrictive transfusion trigger, erythropoietin significantly avoids transfusion, however, at unacceptably high costs. Autologous blood salvage devices were not effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…It was thus concluded that EPO and perioperative blood salvage were not cost-effective in primary elective THA and TKA. For the use of EPO and perioperative blood salvage in revision THA and TKA no conclusions about the (cost-) effectiveness could be drawn [18,19]. These results are in line with recent literature.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…It was thus concluded that EPO and perioperative blood salvage were not cost-effective in primary elective THA and TKA. For the use of EPO and perioperative blood salvage in revision THA and TKA no conclusions about the (cost-) effectiveness could be drawn [18,19]. These results are in line with recent literature.…”
Section: Introductionsupporting
confidence: 65%
“…This study is the next step following a RCT on EPO and perioperative blood salvage as transfusion alternatives in THA and TKA using a restrictive transfusion policy, showing that use of these BSMs is not cost-effective [18,19], and a study in which a tailored de-implementation strategy was systematically developed [25,30,34]. Given the large number of THA and TKA performed annually in the Netherlands and worldwide, de-implementation of non-cost effective BSMs contributes to more efficient healthcare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its role in blood loss management has been thoroughly studied, showing a 60% reduction of ABTs in patients who received EPO compared to control group[28-30]. Three or four weekly subcutaneous injections (600 IU/kg) seems to be the most frequently used protocol with the best results[31-35]. Weber et al[36] reports a mean rise in pre-operative Hb of 1.9 g/dL in patients that received EPO.…”
Section: Pre-operativementioning
confidence: 99%
“…Recently, some studies have found that it was little or no advantage. So-Osman et al 2 found that there was no significant increase in hemoglobin level after total knee arthroplasty in the IBS group, and it could not reduce the transfusion of allogeneic blood. Other studies also reported that IBS did not reduce the rate of allogeneic blood transfusion and the volume of blood transfusion 3 days postoperatively.…”
Section: Introductionmentioning
confidence: 97%